The Role of Law as a Regulatory Instrument for Artificial Intelligence Ethics in Indonesia - Alirahman, Iman (Jurnal Ilmiah Hukum dan Keadilan, 2026)
This study aims to analyze the importance of the role of law in regulating the ethics of artificial intelligence (AI), which has begun to develop rapidly in Indonesia. The development of artificial intelligence cannot be allowed to proceed in an uncontrolled manner without a clear ethical framework and legal regulations governing it. Therefore, the concept of artificial intelligence ethics is required as a normative foundation for the use and development of AI. Artificial intelligence ethics is a field of study that examines moral principles and values that must be considered in the utilization and development of AI technology. In this context, law plays a crucial role as an instrument that provides legal certainty, limitations, and guidance in the implementation of artificial intelligence ethics in Indonesia.